1994
DOI: 10.1002/ijc.2910590502
|View full text |Cite
|
Sign up to set email alerts
|

Preserved foods and nasopharyngeal carcinoma: A case‐control study among singapore chinese

Abstract: The association between the consumption of preserved foods in infancy, childhood and adulthood and the risk of nasopharyngeal carcinoma was investigated in a case-control study among Singapore Chinese: 200 cases (73% male) were compared with 406 hospital controls (71% male). Significantly increased risks were observed in association with frequent adult consumption of salted soy beans (OR 7.3 for consumption 4 or more times per week, compared with never), canned pickled vegetables (p = 0.01; OR 4.5 for 4 or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 11 publications
4
40
0
Order By: Relevance
“…34 Twelve studies stated that the NPC cases under study were histologically confirmed. 14,31-34,37-42 The source of controls was populationbased in 11 studies, 12,14,[32][33][34][35][36][37]40,42,43 hospital-based in 4 studies 13,31,38,39 and not stated in 1 study. 41 Thirteen studies were conducted among Chinese residents of Asian countries; of these, 9 were conducted in China 12,31,34,35,[37][38][39][40][41] and the others were carried out in Taiwan, 33 Malaysia, 14,43 and Singapore.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…34 Twelve studies stated that the NPC cases under study were histologically confirmed. 14,31-34,37-42 The source of controls was populationbased in 11 studies, 12,14,[32][33][34][35][36][37]40,42,43 hospital-based in 4 studies 13,31,38,39 and not stated in 1 study. 41 Thirteen studies were conducted among Chinese residents of Asian countries; of these, 9 were conducted in China 12,31,34,35,[37][38][39][40][41] and the others were carried out in Taiwan, 33 Malaysia, 14,43 and Singapore.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…41 Thirteen studies were conducted among Chinese residents of Asian countries; of these, 9 were conducted in China 12,31,34,35,[37][38][39][40][41] and the others were carried out in Taiwan, 33 Malaysia, 14,43 and Singapore. 13 The remaining 3 studies were conducted in the United States, 36 Algeria, 32 and Tunisia. 42 Dietary intake information was collected using a food-frequency questionnaire in 12 studies, [12][13][14]31,[33][34][35][36][37][40][41][42] a dietary history questionnaire in 2 studies, 38,39 and dietary recall in 1 study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations